ACUTE TOXICITY TEST OF AMBON BANANA TREE SAP EXTRACT ON MICE (Mus Muculus L.) - Setiawan; Hendri Poernomo; Reza Pramana (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Banana tree sap is commonly used by the community as herbal medicine in the process of accelerating wound healing so it needs to be tested for the safety of its use. The research entitled Test of Acute Toxicity and Allergy of Ambon Banana Tree Sap Extract to Mice (Mus Muculus L.) aims to determine Lethal Dose 50, toxicity classification and to observe allergic symptoms dermally of Ambon banana tree sap extract to mice. Materials and Methods: In the acute toxicity test using the Thomson Weil calculation method using mice as experimental animals as many as 25 which were divided into 5 treatment groups with the main test series group I as the control group with 0.3% Na-CMC, groups 2-5 were given the test extract with doses of 300, 600, 1200 and 2400mg/kgBW with one oral administration and observed the number of deaths in each test animal for 14 days. Results and Discussions: In allergy testing using the Wilocoxon method. From the results of the acute toxicity test study, the LD50 value of banana tree sap extract was 1116.8mg/kgBW (1.116g/kgBW) included in the moderate toxic category (0.5-5g/kgBW) and in the allergy test it did not cause allergies (no rash and red-red). For acute toxicity, the weights of mice were analyzed using the ANOVA and LSD tests as well as the allergy test using Wilocoxon. The results of the analysis show that there is a significant difference at the test level of 0.05 (???? <0.05). in the allergy test obtained statistical test results which stated that there was no allergic reaction in mice during treatment with a ???? value of 1.000 > 0.05. Conclusion: Giving banana tree sap extract at certain doses can cause death in mice but does not cause any allergic symptoms.